Lessons of ALS imaging: Pitfalls and future directions - A critical review - BEDE, PETER; HARDIMAN, ORLA (My University, 2014)
Background: While neuroimaging in ALS has gained unprecedented momentum in recent years, little progress has been made in the development of viable diagnostic, prognostic and monitoring markers. Objectives: To identify and discuss the common pitfalls in ALS imaging studies, and to reflect on optimal study designs based on pioneering studies. Methods: A ?PubMed?-based literature search was performed in ALS based on neuroimaging-related keywords. Study limitations were systematically reviewed and classified so that stereotypical trends could be identified. Results: Common shortcomings, such as relatively small sample sizes, statistically underpowered study designs, lack of disease controls, poorly characterized patient cohorts and a large number of conflicting studies remain a significant challenge to the field. Imaging data of ALS continue to be interpreted at a group-level, as opposed to meaningful individual-patient inferences. Conclusions: A systematic, critical review of ALS imaging has identified stereotypical shortcomings, the lessons of which should be considered in the design of future prospective MRI studies. At a time when large multicentre studies are underway a candid discussion of these factors is particularly timely.
PUBLISHED
PMID: 24624329
Keywords: Amyotrophic lateral sclerosis; Biomarker